Short-term, daily intake of yogurt containing Bifidobacterium animalis ssp. lactis Bf-6 (LMG 24384) does not affect colonic transit time in women. Issue 2 (28th January 2014) - Merenstein, Daniel J.; D'Amico, Frank; Palese, Caren; Hahn, Alexander; Sparenborg, Jessy; Tan, Tina; Scott, Hillary; Polzin, Kayla; Kolberg, Lore; Roberts, Robert
<x content-type="archive" xml:space="preserve">Abstract</x> The present study investigated the effect of Bifidobacterium animalis ssp. lactis Bf-6 (LMG 24 384) (Bf-6)-supplemented yogurt on colonic transit time (CTT). A triple-blinded, randomised, placebo-controlled, two-period cross-over trial was conducted with sixty-eight women with a self-reported history of straining during bowel movements or hard or lumpy stools in the past 2 years. As per regulatory requirements for probiotic studies, eligible women were generally healthy and not actively constipated at the time of enrolment. Participants consumed both Bf-6 and placebo yogurts for 14 d each in a randomised order, with a 6-week washout period between the treatments. The primary outcome, CTT, was assessed via Sitz marker X-rays. The average CTT was 42·1 h for the active period and 43·3 h for the control period (mean difference 1·2 h, 95 % CI − 4·9, 7·4). Since the statistical tests for the cross-over study implied that the mean CTT for the active and control periods in period 2 were biased, the standard protocol suggests examining the results of only period 1 as a traditional randomised controlled trial. This showed that the mean CTT was 35·2 h for the active period v. 52·9 h for the control period (P= 0·015). Bootstrapping demonstrated that both the mean and median differences remained significant (P= 0·016 and P= 0·045, respectively). Few adverse events were noted, with no differences among the active and control periods. The paired analysis showed no differences between the active and control periods during the cross-over trial. Further trials should be conducted in populations with underlying problems associated with disordered transit to determine the potential value of probiotic supplementation more accurately.